Nuclear Deadlock, Stalled Diplomacy: The Northeast Asia Nuclear Weapon Free Zone Alternative – Proposals, Pathways, Prospects - Michael Hamel-Green (Journal for Peace and Nuclear Disarmament, 2021)
The current nuclear deadlock with North Korea remains unresolved as the initially promising 2018–2019 three-way diplomacy between the DPRK, US and ROK stalls. More widely in Northeast Asia, nuclear confrontation between China and the US is mounting, with increased deployment of nuclear-weapon-capable forces in and around the region, including land and sea-based missiles, missile defence systems, and deployment of non-strategic nuclear weapons on mobile platforms. The paper proposes that an alternative to continuing nuclear escalation, and the increasing threat of a nuclear catastrophe, does exist in the shape of a phased establishment of a regional Northeast Asian NuclearWeapon Free Zone (NWFZ) and regional comprehensive security agreement involving a final peace settlement of the Korean War, establishment of a regional security forum, economic and energy assistance to the DPRK, and legally binding security guarantees. The paper discusses NWFZ precedents in other regions and past proposals for such a zone in Northeast Asia. It examines the special NWFZ features required in this region, including rigorous verification of the dismantlement of existing nuclear weapons and facilities in the DPRK, a Korean War peace settlement, a flexible NWFZ entry into force mechanism that gives time for DPRK to assess the security guarantee benefits of the NWFZ zone, and provisions for preventing forward deployment of non-strategic nuclear weapons within the region. The paper concludes by presenting NEANWFZ proposals emerging from a recent Northeast Asian workshop of regional experts, and identifying potential pathways, advocates, and prospects for its successful negotiation in the current global context.